Thermoreversible Gels Based on Chitosan Copolymers as "Intelligent" Drug Delivery System with Prolonged Action for Intramuscular Injection - Igor D. Zlotnikov; Stanislav M. Malashkeevich; Natalia G. Belogurova; Elena V. Kudryashova (MDPI AG, 2023)
Thermosensitive gels based on copolymers (PEG-chitosan, chitosan-polyethylenimine, chitosan-arginine and glycol-chitosan-spermine) are presented as promising polycations for the formation of DNA polyplexes and the potential for the development of drugs with prolonged release (up to 30 days). Being in liquid form at room temperature, such compounds can be injected into muscle tissue with rapid gel formation at human body temperature. An intramuscular depot is formed with a therapeutic agent that provides a gradual release of the drug, such as an antibacterial or cytostatic. The physico-chemical parameters of the formation of polyplexes between polycationic polymers of various compositions and molecular architecture and DNA were studied via FTIR, UV-vis and fluorescence spectroscopy using the dyes rhodamine 6G (R6G) and acridine orange (AO). The competitive displacement of AO from AO-DNA complexes showed that, with a ratio of N/P = 1, most of the DNA is bound to a polycation. During the formation of polyplexes, the DNA charge is neutralized by a polycation, which is reflected in electrophoretic immobility. The cationic polymers described in this work at a concentration of 1-4% are capable of forming gels, and the thermoreversible property is most characteristic of pegylated chitosan. BSA, as a model anionic molecule, is released by half in 5 days from the Chit5-PEG5 gel; full release is achieved in 18-20 days. At the same time, in 5 days, the gel is destroyed up to 30%, and in 20 days, by 90% (release of chitosan particles). For the first time, flow cytometry was used to study DNA polyplexes, which showed the existence of fluorescent particles in a much larger number in combination with free DNA. Thus, functional stimulus-sensitive polymers are potentially applicable for the creation of prolonged therapeutic formulations for gene delivery systems, which were obtained. The revealed regularities appear to be a platform for the design of polyplexes with controllable stability, in particular, fulfilling the requirements imposed for gene delivery vehicles.